Soil Quality Index Mapping Using GIS and Sentinel-2 Image in Jember, East Java - Putri Tunjung Sari; Indarto Indarto; Marga Mandala (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Soil is a solid mineral and organic matter from weathering rocks over the years. The current condition shows many productive lands that are of low quality. Soil quality must be a top priority in land management efforts to support the sustainability of ecology. This study proposes to soil quality index (SQI) assessment of paddy fields in Jember Regency, Indonesia, using the principal component analysis (PCA) method based on spatial data. The research procedure consists of (1) making land units, (2) soil sampling, (3) laboratory analysis, (4) principal component analysis (PCA), (5) assessment of soil quality index (SQI), and (6) Thiessen polygon analysis. The correlation results show the average correlation value < 0.5 (not significant). The soil quality is determined by three main components: total P, silt fraction, and clay fraction. The results of the soil quality analysis showed that 68,888 Ha was in the very low-quality category, and 39,948 Ha was in the low-quality category. Meanwhile, paddy fields included in the medium category are only 3,513 Ha. The addition of organic matter can improve the quality of paddy fields.